2015
DOI: 10.1039/c5nj01127b
|View full text |Cite
|
Sign up to set email alerts
|

Electrically conductive polyaniline sensitized defective-TiO2for improved visible light photocatalytic and photoelectrochemical performance: a synergistic effect

Abstract: nanocomposites were prepared by the in-situ oxidative polymerization of aniline in the presence of TiO 2 (p-TiO 2 and m-TiO 2 ) nanoparticles followed by sulfonation with fuming sulfuric acid. Defect-induced TiO 2 (m-TiO 2 ) nanoparticles were obtained by an electron beam (EB) treatment of commercial TiO 2 (p-TiO 2 ) nanoparticles. The resulting s-Pani@p-TiO 2 and s-Pani@m-TiO 2 nanocomposites were characterized by UV-visible diffuse absorbance spectroscopy, photoluminescence spectroscopy, transmission electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 35 publications
1
8
0
3
Order By: Relevance
“…The contact angle of water droplets on graphene and graphene-TiO2 films are shown in Figure S5, where it is found that graphene-TiO2 film is highly wetting (small contact angle) and therefore superhydrophilic. This is due to the hydrogen bonding and strong interlinking between Ti-O and unsaturated -O and -OH groups on graphene [12,[40][41][42]. It is known that TiO2 surface is self-cleaning, meaning that it removes the surface dirt, such as organic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The contact angle of water droplets on graphene and graphene-TiO2 films are shown in Figure S5, where it is found that graphene-TiO2 film is highly wetting (small contact angle) and therefore superhydrophilic. This is due to the hydrogen bonding and strong interlinking between Ti-O and unsaturated -O and -OH groups on graphene [12,[40][41][42]. It is known that TiO2 surface is self-cleaning, meaning that it removes the surface dirt, such as organic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of photoelectric catalytic water splitting on low‐cost, nontoxic, and stable TiO 2 electrodes, various bandengineering strategies have been attempted to narrow the bandgap of TiO 2 to harvest a larger portion of solar energy in the visible light region . Doping with transition metal and/or nonmetal ions, creating structure defects through hydrogenation, surface metallization, and hybridization with low‐bandgap semiconductors have been used as effective strategies . Among these methodologies, N doping has been considered as a promising solution because it can be used to extend the visible light absorption, it has desirable photocatalytic activity, and acceptable level of recombination of photogenerated charge carriers .…”
Section: Introductionmentioning
confidence: 99%
“…As transferên-cias dessas cargas e a formação de sítios oxidantes e redutores também ocorrem de forma similar àquela para UV (Figura 4). [62][63][64][65][66] Em sistemas solares quando uma parcela de radiação UV está presente, ou ainda, com o uso de radiação artificial sem filtros, haverá contribuição de ambos os mecanismos propostos para luz visível e ultravioleta. 13 Os estudos que envolvem apenas luz UV ou visível são importantes justamente porque em sistemas solares ambas estão presentes, e por isso é preciso compreender como os catalisadores formados por PANI respondem a cada uma delas.…”
Section: Polianilinaunclassified
“…6,14,15,43,52,54,55,61,[75][76][77][78] A determinação da fotocorrente gerada pelo catalisador e a conversão de fóton incidente em corrente (IPCE) também estão relacionadas diretamente com a maior eficiência fotocatalítica de catalisadores compósitos. 9,52,54,66,76,78,79 Deng et al 78 mostraram que catalisador PANI.TiO 2 -microesfera foi capaz de gerar cerca de 0,11 μA cm -2 em fotocorrente e remoção de corantes acima de 95% sob luz visível, enquanto que, apenas TiO 2 -microesfera em torno de 0,03 μA cm -2 e 60 a 70% de remoção de corantes. No estudo feito por Li et al 52 com PANI.TiO 2 -nanotubos na remoção de rodamina b sob luz visível, dentre todos os materiais sintetizados, aquele com maior geração de fotocorrente (6 μA cm -2 ) promoveu maior remoção do corante, cerca de 90%.…”
Section: Polianilinaunclassified
See 1 more Smart Citation